2015
DOI: 10.1002/sdtp.10022
|View full text |Cite
|
Sign up to set email alerts
|

P‐2: A Novel Method for LTPS Model Extraction with Hysteresis and Transient Current Analysis

Abstract: Time-sampling measurements are used in this paper to build time dependent LTPS TFT current model. The device model that considers bias and time dependent threshold voltage (V th ) shift and mobility degradation is implemented in Eldo through GUDM for simulating a pixel circuit as an indicator of panel performance. Author Keywordstime-sampling measurement, LTPS, V th shift, mobility degradation, Eldo, GUDM, transient current. Objective and BackgroundThe performance of a low-temperature poly-silicon (LTPS) thin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…TFT exhibited different drain current at the same gate voltage depending on the gate sweep direction. The mechanisms was attributed to the electron trapping/detrapping processes associated with the deep-level traps in the grain boundaries of the poly-Si channel and the hole trapping/detrapping into/from the gate oxide defects [5] .…”
Section: Analysis Of Tft Hysteresis Effectmentioning
confidence: 99%
“…TFT exhibited different drain current at the same gate voltage depending on the gate sweep direction. The mechanisms was attributed to the electron trapping/detrapping processes associated with the deep-level traps in the grain boundaries of the poly-Si channel and the hole trapping/detrapping into/from the gate oxide defects [5] .…”
Section: Analysis Of Tft Hysteresis Effectmentioning
confidence: 99%
“…Some of previous researches have reported that hysteresis phenomenon of driving TFTs, resulting in a threshold-voltage (Vth) shift, can be the main cause of short-term image sticking. [3,5] In order to evaluate the image sticking level from the perspective of TFT characteristics, here we developed a new method named just noticeable current difference (JND_Current) based on transient response time test of TFTs. [15] JND_Current can be extracted according to equation ( 6) by replacing display brightness with gray current of TFTs.…”
Section: Image Stickingmentioning
confidence: 99%
“…Many groups have reported that short-term image sticking can be greatly improved by reducing hysteresis. [3][4][5] However, there are few reports focused on what exactly TFT characteristics is useful upon the evaluation of short-term image sticking.…”
Section: Introductionmentioning
confidence: 99%
“…[7] The measurement of the transient-IDS and the serial DC stressed I-V characteristics showed that the hysteresis was originated from both of the threshold voltage shift and mobility degradation. [8] Also, there were many trials to reduce the hysteresis. The followings are summary of the previously reports.…”
Section: Introductionmentioning
confidence: 99%